Electroencephalogram Source Imaging and Brain Network Based Natural Grasps Decoding - Xu, Baoguo; Deng, Leying; Zhang, Dalin; Xue, Muhui; Li, Huijun; Zeng, Hong; Song, Aiguo (Frontiers in Neuroscience, 2021)
Studying the decoding process of complex grasping movement is of great significance to the field of motor rehabilitation. This study aims to decode 5 natural reach-and-grasp types using sources of movement-related cortical potential (MRCP) and investigate their difference in cortical signal characteristics and network structures. Electroencephalogram (EEG) signals were gathered from 40 channels of 8 healthy subjects. In an audio cue-based experiment, subjects were instructed to keep no-movement condition or perform 5 natural reach-and-grasp movements: palmar, pinch, push, twist and plug. We projected MRCP into source space and used average source amplitudes in 24 regions of interest as classification features. Besides, functional connectivity was calculated using phase locking value. Six-class classification results showed that a similar grand average peak performance of 49.35% can be achieved using source features, with only two-thirds of the number of channel features. Besides, source imaging maps and brain networks presented different patterns between each condition. Grasping pattern analysis indicated that the modules in the execution stage more focus on internal communication than in the planning stage. The former stage was related to the parietal lobe, while the latter was associated with the frontal lobe. This study demonstrates the superiority and effectiveness of source imaging technology and reveals the spread mechanism and network structure of 5 natural reach-and-grasp movements. We believe that our work will contribute to the understanding of the generation mechanism of grasping movement, and promote a natural and intuitive control of BCI.